DESIGN OF A BATIK MACHINE BASED ON CABLE-DRIVEN PARALLEL ROBOT FOR PENDULUM PATTERN MAKING PROCESS - Juwandana, Alfisena
Batik is Indonesia's cultural heritage that has been esteemed for its artistic value. One of the most notable innovations in batik patterns was created by Komarudin Kudiya, who developed the technique of pendulum batik. A pendulum batik combines harmonograph trajectory patterns and traditional batik ornaments. In manufacturing, a pendulum filled with wax is swung at a specific angle and thrust. The process of creating pendulum batik frequently results in patterns that do not align or overlap, necessitating repetition. The resulting pattern is also unique and cannot be replicated. To automate the pendulum pattern-making process, the Cable-Driven Parallel Robot (CDPR) was selected due to its high flexibility and ability to cover a wide working area. An under-constrained CDPR type with four cables is employed to enhance the utilization of space when the machine is not in use. This research presents the development of a pendulum batik machine using the spiral development method. The research commences with an analysis of the system requirements and the general architecture of the machine. The machine design was conducted by the VDI 2206 method. The machine construction generally comprises a guiding head (GH) and a funnel. The guiding head (GH) is constructed using a revolute joint system that ensures its alignment with the cable vector in the x and y axes. Furthermore, the cable winding system is also considered to prevent the overlapping of cables. Furthermore, an analysis of the maximum (Fmax) and minimum (Fmin) stresses is conducted to determine the safety factors and feedback parameters based on the machine's and the cables' specifications. The maximum (Fmax) and minimum (Fmin) values are 101.94 N and 0.1 N, respectively. Subsequently, an analysis of kinematics equations using inverse kinematics is conducted to regulate the movement of the funnel, with the input being the coordinates to be addressed. Furthermore, the kinematics analysis incorporates the revolute joint and cable winding systems. The batik pendulum machine is operated architecturally using a special application on a tablet. This application designs the pendulum pattern based on the spherical pendulum equation. The output of this application is an array of pendulum pattern coordinates, which are then sent to the master microcontroller via a WiFi network. In the master microcontroller, inverse kinematic and movement speed calculations are performed. The results of these calculations are then sent to each microcontroller at each GH. Machine testing examines both static and dynamic characteristics. Static characteristic testing assesses the accuracy and repeatability of each GH and the movement of the machine funnel. Dynamic testing determines the optimal wax temperature and engine movement speed. In static characteristic testing, accuracy testing is conducted by measuring the movement of the motor against the length of the rope, with the influence of varying loads. The two loads utilized are 1 kg and 3 kg. The average root mean square error (RMSE) values for loads one and two were 0.284 mm and 1.05 mm, respectively. Repeatability testing was only conducted with the second load. The average RMSE value for repeatability testing was 0.185 mm. Funnel movement testing was conducted using a circle track with a radius of 0.3 m and a box track with a length of 1 m and a width of 0.5 m. Tests were performed by flowing wax on the fabric, and the trajectory formed was subsequently measured. The root mean square error (RMSE) values for the circle and box trajectories were 0.4463 mm and 0.4677 mm, respectively, with a maximum absolute error (MAE) value of 2.5 mm. In dynamic testing, an attempt was made to identify the optimal wax temperature by creating a spiral pattern with temperature variations in the range of 75 to 85 degrees Celsius at a constant speed of 100 millimeters per second. The optimal temperature selection is based on the penetrating power of the wax on the fabric and the width of the resulting pattern. The optimal temperature was between 78 and 82 degrees Celsius, as this temperature range yielded patterns that were not excessively wide and could be readily absorbed into the fabric. Movement speed tests were conducted with variations between 50 and 150 mm/s, maintaining a constant wax temperature of 78°C. The test results indicated that the maximum (vmax) and minimum (vmin) speeds were 125 mm/s and 75 mm/s, respectively. Once the maximum and minimum speeds have been determined, speed regulation is carried out by the characteristics of the spherical pendulum equation. The movement speed is adjusted according to the normalized pendulum movement speed to reduce the funnel's vibration and improve the resulting pattern's quality.